Chapter Analysis and survey of Lake Garda lemon houses: a tool to understand and manage a Mediterranean landscape in Lombardy - Cazzani, Alberta (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Lake Garda microclimate allowed the settlement and flourishing of a peculiar cultivation, that of the limonaie (lemon houses), which during its splendour exported citrus all over Central and Northern Europe. We highlight how, in order to preserve this unique cultural heritage, there is an urgent need of a census accounting for both the current condition of the ancient productive sites and for all the agroecosystemic relationships between the limonaie, which contributed to shape their landscape. A particular attention is devoted to the traditional water harvesting and irrigation structures